The Language of the Social Media Impact on Global Supply Chain Management - Nurhayati, Nurhayati; Munirah, Munirah; Hasyim, Muhammad; Kaharuddin, Kaharuddin (ExcelingTech, 2020)
Abstract- Social media is driving the rethinking of many of the principles of economics. The use of social media within supply chains is lagging behind their usage for other operational functions, however supply chain management is evolving into supply chain management 2.0. The purpose of this article is to provide researches of the supply chain management a reference with the main concepts of social media: social profiles, social applications, brand outposts and communities, and the social ecosystem. This study used descriptive method data collection method used was listening method. Unique morpheme is a morpheme with typical features divergent from other morphemes or language morpheme in general. The finding is useful for social and supply chain interaction especially morphological studies in social media